Application of freeze-dried Enterococcus faecium NRRL B-2354 in radio-frequency pasteurization of wheat flour. (April 2018) - Xu, Jie; Liu, Shuxiang; Tang, Juming; Ozturk, Samet; Kong, Fanbin; Shah, Devendra H.
Abstract: This study aimed to assess the applicability of freeze-dried E. faecium NRRL B-2354 (FDE) to evaluate the inactivation efficiency of radio-frequency (RF) pasteurization on wheat flour. FDE was prepared by adding equal volume of 10% skim milk solution as a protectant. Microstructure of FDE was evaluated by scanning and transmission electron microscopy. Thermal resistance parameters of FDE in wheat flour were determined at 75 °C, 80 °C, and 85 °C. A 6 kW, 27.12 MHz RF heating system was used to rapidly pasteurize 3.0 kg wheat flour at 75 °C, 80 °C, and 85 °C, respectively. Population reduction of FDE in the geometric center of flour samples were compared with survivor counts and predicted model. Flour samples were equilibrated to water activity 0.45 measured at 25 °C. The results showed that FDE protected by skim milk were well maintained with repeatable D-values D75°C = 14.27 ± 0.85 min, D80°C = 5.92 ± 0.39 min, and D85°C = 2.79 ± 0.15 min, and z-value of 13.1 °C. RF treatment at 75 °C, 80 °C, and 85 °C for 10 min achieved 1.0-, 2.5-, and 4.9-log reduction of FDE, respectively. In RF pasteurization process, the dynamic population reduction of FDE can be predicted by a model based on F-value. RF treatment provides an effective and rapid approach to inactivate target microorganism in flour samples. Highlights: Skim milk protected freeze-dried E. faecium NRRL B-2354 was used as an alternative form of inoculum in low-moisture foods. RF heating can reduce up to 4.93-log CFU/g of E. faecium NRRL B-2354 in bulk wheat flour sample within 27 min. Inactivation kinetics of E. faecium NRRL B-2354 can be predicted by a model based on F-value during RF heating.